Layanan pendidikan berbasis digital: Upaya pemenuhan hak penyandang disabilitas di perguruan tinggi - nurkomaria, nurkomaria nurkomaria (Maliki Interdisciplinary Journal, 2026)
The advancement of digital technology has had a significant impact on the field of education, including the provision of educational services for students with disabilities in higher education institutions. Ensuring the right to education without discrimination is part of Human Rights that must be guaranteed by both the state and educational institutions. This study aims to examine the implementation of digital-based educational services for students with disabilities in universities and to identify various challenges that arise during their implementation. The research employs a normative juridical method with a qualitative descriptive approach through literature studies and analysis of various regulations concerning inclusive education. The findings indicate that the use of digital technology, such as online learning systems, accessibility support applications, sign language interpreters, and adaptive learning platforms, can expand educational access for students with disabilities. However, the implementation of digital-based educational services still faces several challenges, including limited facilities and infrastructure, low awareness among educational institutions, a lack of supporting personnel, and the inadequate availability of digital accessibility facilities. Therefore, synergistic cooperation between the government, universities, and society is needed to create a digital-based inclusive education system capable of ensuring equal educational rights for all students without discrimination.